The Impact Of IT And Multimedia On Teaching And Learning Process At MMU - Peresamy, P., Rajandran (2002)
This research will evaluate most of the IT and Multimedia based facilities, approaches, techniques and teaching methods being implemented in delivering lectures at MMu, for examples, the web based learning, online notes, MMLS, multimedia presentations, and dircet internet access in teaching.